Insulin-inducible THRSP maintains mitochondrial function and regulates sphingolipid metabolism in human adipocytes - Maria A. Ahonen; Marcus Höring; Van Dien Nguyen; Sami Qadri; Juuso H. Taskinen; Meghana Nagaraj; Martin Wabitsch; Pamela Fischer-Posovszky; You Zhou; Gerhard Liebisch; P. A. Nidhina Haridas; Hannele Yki-Järvinen; et al. (BMC, 2022)
Abstract Background Thyroid hormone responsive protein (THRSP) is a lipogenic nuclear protein that is highly expressed in murine adipose tissue, but its role in humans remains unknown. Methods We characterized the insulin regulation of THRSP in vivo in human adipose tissue biopsies and in vitro in Simpson-Golabi-Behmel syndrome (SGBS) adipocytes. To this end, we measured whole-body insulin sensitivity using the euglycemic insulin clamp technique in 36 subjects [age 40 ± 9 years, body mass index (BMI) 27.3 ± 5.0 kg/m2]. Adipose tissue biopsies were obtained at baseline and after 180 and 360 min of euglycemic hyperinsulinemia for measurement of THRSP mRNA concentrations. To identify functions affected by THRSP, we performed a transcriptomic analysis of THRSP-silenced SGBS adipocytes. Mitochondrial function was assessed by measuring mitochondrial respiration as well as oxidation and uptake of radiolabeled oleate and glucose. Lipid composition in THRSP silencing was studied by lipidomic analysis. Results We found insulin to increase THRSP mRNA expression 5- and 8-fold after 180 and 360 min of in vivo euglycemic hyperinsulinemia. This induction was impaired in insulin-resistant subjects, and THRSP expression was closely correlated with whole-body insulin sensitivity. In vitro, insulin increased both THRSP mRNA and protein concentrations in SGBS adipocytes in a phosphoinositide 3-kinase (PI3K)-dependent manner. A transcriptomic analysis of THRSP-silenced adipocytes showed alterations in mitochondrial functions and pathways of lipid metabolism, which were corroborated by significantly impaired mitochondrial respiration and fatty acid oxidation. A lipidomic analysis revealed decreased hexosylceramide concentrations, supported by the transcript concentrations of enzymes regulating sphingolipid metabolism. Conclusions THRSP is regulated by insulin both in vivo in human adipose tissue and in vitro in adipocytes, and its expression is downregulated by insulin resistance. As THRSP silencing decreases mitochondrial respiration and fatty acid oxidation, its downregulation in human adipose tissue could contribute to mitochondrial dysfunction. Furthermore, disturbed sphingolipid metabolism could add to metabolic dysfunction in obese adipose tissue.